The contributing of chemistry learning in supporting education for sustainable development: A systematic literature review - Adek Diah Murti; Hernani Hernani (Jurnal Pendidikan Kimia (JPKIM), 2023)
This study aimed to examine the contribution of chemistry learning in supporting Education for Sustainable Development (ESD) and the types of competencies that can be developed through ESD. The method used is Systematic Literature Review (SLR), which consists of five stages, namely question formulation, locating studies, study selection and evaluation, analysis and synthesis, reporting and using the results. Based on a study of 38 journal articles from International and National Journal, the contribution of chemistry learning in supporting ESD is manifested in the form of integrating ESD concepts into learning models, incorporating ESD concepts in a chemistry learning context, and developing ESD concepts through learning designs and teaching materials. Through the implementation of ESD in chemistry learning, competencies that can be developed are communication, collaboration, problem solving, creative thinking, systems thinking, critical thinking, scientific literacy, sustainable environmental literacy, understanding, motivation, environmental awareness, and sustainable awareness. Chemistry education and ESD have strong link in many aspects of life, so that competencies developed through the implementation of ESD in the learning process will be able to improve the quality of education and environment.Keywords: A systematic literature review; Contributing of chemistry learning; Education for sustainable development